Factors affecting customers' satisfaction in Arabic restaurants - Omar, M.S.; Ariffin, H. F.; Ahmad, Rozila (2014)
Restaurant concept plays an important role in establishing and running a business.This study focuses on the factors affecting customers‟ satisfaction in Arabic restaurants.There are two objectives of this research: 1. to examine the relationships between food quality, service quality, and restaurant ambience with customer satisfaction 2. to determine which restaurant attribution that highly influence customers‟ satisfaction in Arabic restaurants.The data have been collected through sets of questionnaire answered by 411 respondents who are Arabic restaurant customers in Shah Alam, Selangor, Malaysia.The result shows that all variables have relationships with customers' satisfaction.The result also indicates restaurant ambiance attributes the most to customer satisfaction. Managerial implications, limitations and future research directions are also discussed.